Ab-initio calculations of the electronic properties of pure and cobalt doped MgF 2 - Дукенов, А.Б.; Усеинов, А.Б.; Акылбеков, А.Т.; Даулетбекова, А.К.; Здоровец, М.В.; Ыбыраев, Н.С.; Оралбеков, Н.Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
A deep understanding of the spectral characteristics of materials plays a high role in the development of solid-state laser systems. In our work, quantum-chemical modeling of the electronic and optical properties of a MgF 2 crystal doped with cobalt (Co) for laser applications in the Crystal program has been carried out.As a result of calculations, it has been shown that the cobalt atom in MgF 2 is in a high-spin quantum state (with spin 3), and creates a strong ion-covalent bond with the crystal lattice.The calculated projected density of the 3d states of the Co atom gives good agreement with the observed experimental absorption spectrum in the arrangement of the electronic transition levels.Thus, this computational method makes it possible to qualitatively (and in particular cases quantitatively) describe the spectral characteristics of doped dielectric materials. And also, this method of calculation can be used in subsequent similar studies.